Characterization and property enhancement of chromic oxide reinforced to Al LM26 metal matrix composite - Shambulingamurthy Gowdagere Chikkalingaiah; Girish Kanuvanahalli Bettaiah; M Hareesha; Chandrakant R. Kini (Cogent Engineering, 2025)
This study shows a new way to improve the mechanical properties of the aluminium LM26 alloy by adding chromium oxide as a reinforcement. Instead of using traditional reinforcements, chromium oxide is added in different amounts (2.5% to 10%) to make a high-performance metal matrix composite that can be used in industries like defense, aerospace, and automotive. The microstructural analysis indicated that the chromium oxide particles were evenly distributed, improving mechanical properties. The study found that hardness (38.27%), compressive strength (20.55%), impact strength (34%), and tensile strength (43.48%) all improved significantly with higher chromium oxide wt.%. This work demonstrates its potential for high-strength, lightweight applications. This study bridges a significant research gap by demonstrating the potential of chromium oxide as a reinforcement for advanced aluminium composites.